The Effectiveness of Herbion Iceland Moss Syrup in the Treatment of Dry Cough in Children - S.L. Niankovskyi; M.S. Yatsula; I.V. Babik; V.B. Yaskiv; O.I. Shpychka; B.V. Yandio (Zaslavsky O.Yu., 2016)
The article presents the etiologic and pathogenetic aspects of the appearance of dry cough in children. Personal experience of using Herbion Iceland moss syrup in the treatment of post-infectious dry cough in children aged 4-10 years is described. Application of the drug has significantly reduced the intensity of dry cough, quickly stopped night coughing, improved the quality of life of children. Herbion Iceland moss syrup is well tolerated by children and does not cause adverse reactions when used.